Barrier swaption pricing formulae of mean-reverting model in uncertain environment. (July 2022) - Lu, Jing; Yang, Xiangfeng; Tian, Miao
Abstract: Barrier swaption is an exotic option, in which the option purchaser has the right to decide whether the swaption will come into effect within a period and it becomes effective (invalid) only when the underlying rises (falls) to the barrier price. This paper studies four kinds of barrier swaptions based on the mean-reverting model, which are up-and-in payer swaption, down-and-in receiver swaption, down-and-out payer swaption, up-and-out receiver swaption, and the price calculation formulae are given. Then, the related parameters are calculated by the minimum cover estimation method. Finally, the examples are given. Highlights: This paper investigates the barrier swaption pricing problem in an uncertain environment. Based on the mean-reverting model, four types of pricing formulas are derived. The minimum cover estimation method is used to estimate the parameters of the uncertain differential equation. The corresponding numerical algorithms are given.